1998
DOI: 10.1103/physrevlett.80.5584
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Single Hydrogen Atoms on Si(111)-(7×7) Surfaces

Abstract: Adsorption and diffusion of single hydrogen atoms on Si͑111͒-͑7 3 7͒ surfaces at elevated temperatures have been studied using scanning tunneling microscopy. Hydrogen atoms adsorb preferentially atop rest atoms. An adsorbed H atom can hop between two neighbor rest atoms via an adatom, i.e., via a metastable intermediate state. Below 340 ± C, the hopping is mostly confined within a half-cell, but at higher temperatures, they can hop across the cell boundary. The activation energies for different hopping paths w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 18 publications
6
30
2
Order By: Relevance
“…The hydrogen adsorption and its energetics on the Si(111)-(7×7) surface has been extensively studied before, both experimentally and theoretically, in Refs. [36][37][38]. It has been demonstrated that the H atoms preferentially reside on the rest atom sites.…”
Section: A Nc-afm Imaging Of H Atoms On Si(111)-(7×7)mentioning
confidence: 99%
“…The hydrogen adsorption and its energetics on the Si(111)-(7×7) surface has been extensively studied before, both experimentally and theoretically, in Refs. [36][37][38]. It has been demonstrated that the H atoms preferentially reside on the rest atom sites.…”
Section: A Nc-afm Imaging Of H Atoms On Si(111)-(7×7)mentioning
confidence: 99%
“…Usually, the diffusion of atoms on low-index surfaces is two dimensional and rather isotropic, like in the case of various adsorbates on the Si(111) surface [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the movement of atoms can become strongly anisotropic or even quasi-one-dimensional in the presence of a specific surface reconstruction or on stepped (vicinal) templates [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement can be achieved with commercially available broader bandwidth preamplifiers. Second, the hopping rate can now be measured for individual sites [26,27], as shown presently for the nonequivalent corner and center Siadatom sites. The ability of measuring site-specific hopping rates may further allow us to investigate diffusion heterogeneity, e.g., due to defects, and bring new understanding of the respective interactions.…”
mentioning
confidence: 97%
“…2(c)] showing brighter spots at the corner sites than at the center sites already consistently indicate that the corner Si-adatom site is the most stable adsorption site. While there is no independent data for Cu on this surface available, using a time consuming frame-by-frame imaging procedure, Tsong's group was also able to determine the relative adsorption energies for O 2 [26] and H [27] on the center and corner Si-adatom sites, for which an energy difference of 50 -150 meV was observed.…”
mentioning
confidence: 99%